Analisa Narasi Yehovah Shalom dalam Repetisi Perkataan Tuhan Kepada Gideon Berdasarkan Hakim-Hakim 6:11-24 - Andris Kiamani; Aska Pattinaja (Sekolah Tinggi Teologi Real Batam, 2023)
Judges 6:11-24 contains the life story of Gideon who was chosen by God to judge Israel. In researching this story, there is a special emphasis given by Gideon in response to God's call, by calling Yehovah Shalom. Many studies discuss the story of Gideon only in the context of its thematic structure in Gideon's encounter with God and ignore the deepening of the narrative meaning of Jehovah Shalom, which correlates with the repetition of God's words to Gideon. For this reason, this article is written based on qualitative research with a literature study in a hermeneutic approach, to analyze the narrative of Jehovah Shalom in the repetition of God's words to Gideon. This article finds that there are five important meanings, namely: First, Gideon believed that only God could save the Israelites from the Midianites; Second, Gideon believed that only God could restore the condition of the Israelites that was destroyed due to the colonization of the Midianites; Third, Gideon believed that only God could bless the Israelites so that they would experience prosperity from every poverty; Fourth, Gideon believed that only God could give peace to the Israelites so that Israel could return to a quiet, safe and peaceful life; and Fifth, Gideon believed that only God could choose and call him and give him the strength to be a judge over Israel.Keywords: judges; gideon; repetition; jehovah shalomAbstrakHakim-Hakim 6:11-24 berisi kisah hidup Gideon yang diplih oleh Tuhan untuk menjadi hakim atas Israel. Dalam meneliti tentang kisah ini, ada penekanan khusus yang diberikan oleh Gideon sebagai respon terhadap panggilan Tuhan, dengan menyebut Yehovah Shalom. Banyak penelitian yang membahas kisah Gideon hanya dalam konteks struktur tematisnya dalam perjumpaan Gideon dengan Tuhan dan mengabaikan pendalaman makna narasi Yehovah Shalom, yang berkorelasi dengan repetisi perkataan Tuhan terhadap Gideon. Untuk itulah artikel ini ditulis berdasarkan, penelitian kualitatif dengan studi literatur dalam pendekatan hermeneutik, untuk menganalisa narasi Yehovah Shalom dalam repetisi perkataan Tuhan kepada Gideon. Artikel ini menemukan, ada lima arti penting, yaitu: pertama, Gideon percaya hanya Tuhan yang sanggup menyelamatkan bangsa Israel dari bangsa Midian; kedua, Gideon percaya hanya Tuhan yang dapat memulihkan kondisi bangsa Israel yang hancur akibat penjajahan bangsa Midian; ketiga, Gideon percaya hanya Tuhan yang dapat memberkati bangsa Israel sehingga mengalami kemakmuran dari setiap kemelaratan; keempat, Gideon percaya hanya Tuhan yang dapat memberikan damai sejahtera atas bangsa Israel sehingga Israel dapat kembali hidup tenang, aman dan damai; dan kelima, Gideon percaya hanya Tuhan yang sanggup memilih dan memanggil dirinya serta memberikan kekuatan untuk dapat menjadi hakim atas Israel.Kata Kunci: hakim-hakim; gideon; repetisi; yehovah shalom